Efektivitas Pengiriman Barang di Terminal Peti Kemas (TPK) Koja - Rizka Amalia; Abdul Gani Kamaludin; Asep Ali Tabah (Institut Transportasi dan Logistik Trisakti, 2020)
The purpose of this research is to determine and analyze the effect of loading and unloading performance and the application of auto gates to the effectiveness of shipping goods. Koja Container Terminal is the busiest container terminal compared to other terminals in Indonesia. In this research, the data collection techniques was using observation. The method of data analysis used multiple linear regression equations which one unit of X1 and X2 changes (adding / subtracting) will change the Y percentage either increasing or decreasing. Using the calculation of correlation, it could be seen that the application of auto gate and loading and unloading performance has a very strong and positive relationship to the effectiveness of shipping goods.